(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
Iron deficiency causes anemia in human body. So identification of iron rich rice genotypes as well as biofortification of staple food crops is an effective way to overcome such malnutrition problems. A total of 46 local rice landraces of Bangladesh were used in chemical analysis and DNA fingerprinting to study their ability to synthesize and accumulate iron content in the grain. Rice plants were grown and their grains were collected and digested by acidKNO3:HClO4. iron concentrations were measured from The highest iron content was found Kumra Ghor (168.52ppm) and the lowest in Patnai Balam (0.45 ppm). The SSR markers were used to determine the allelic diversity and relationship among the selected rice germplasms for iron content. Out of 10 SSR primers, 5 primers showed DNA amplification and polymorphism among all the genotypes. Variation was found in number of alleles, allele frequency, Polymorphism Information Content (PIC) and gene diversity. The primer, RM35 having motif (GA) 19 also yielded the highest number of alleles (23) and highest PIC value (0.946). A total of 72 bands were recorded by using 5 SSR primers in all genotypes. The number of alleles per locus ranged from 4 to 23 with an average of 14.40 out of 72 bands. The UPGMA Dendrogram based on Nei’s (1973) genetic distance placed the varieties into 6 distinct clusters. Most of the primers showed the highest Polymorphism Information Content (PIC). Based on this study, the larger range of similarity values using SSR markers provides greater confidence for the assessment of genetic relationships among the varieties. The information obtained from chemical analysis and SSR profiling helps to identify the varieties containing iron content. Genotypes with high iron content could be used as breeding materials to develop nutrient rich rice varieties in order to combat iron deficient problems in population of Bangladesh. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (1), 1-14